Sintesa Precipitated Calcium Carbonate (PCC) Dari Cangkang Kerang Darah ( Anadara Granosa) Dengan Variasi Suhu Kalsinasi Dan Variasi Rasio CaO/HNO3 - Paul Destin Purba; Amun Amri; Zultiniar Zultiniar; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Precipitated Calcium Carbonate (PCC) is a calcium based chemical product that recently has widely utilized in application. The purpose of this research is to obtain PCC at once as the waste problem solver. This research using carbonation method with tested variable were the calcinations temperature and ratio of calcium oxide by nitric acid. The crushed sample were calcined according to the temperature variations (700oC, 800oC, and 900oC). Furthermore, the formed calcium oxide was slacked into the nitric acid according to several calcium oxide by nitric acid ratio (14:300, 17:300, and 20:300 gr/ml). The formed nitric calcium then was added by ammonia to pH 12 to start the synthesis calcium hydroxide. Next subsequent was carbonation, in case flowing calcium hydroxide by carbon dioxide to form white precipitate (PCC). Based on the analysis, the best result of PCC obtained at calcinations temperature of 900oC with the ratio of 14 gr:300 ml that gained 84,88%. The X-Ray Diffraction (XRD) showed that the type of crystals formed were vaterit. The Scanning Electron Microscopy (SEM) showed that the shape of crystals were round (sphere-like) with a relatively uniform size.Keywords: Calcination, carbonation, cockle shell, precipitated calcium carbonate.